INTEGRATION OF TECHNOLOGY IN ISLAMIC BOARDING SCHOOL EDUCATION - Alindra, Bagus Malik; Ubaidillah, Ubaidillah; Hepni, Hepni; Nawangsari, Dyah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This paper aims to analyze the integration of technology in Islamic boarding schools through Rahman's concept of thinking to adapt to the times. Fazlur Rahman criticized Islamic education which is limited in understanding the Qur'an and Sunnah, and emphasized the importance of ethics and curriculum improvement. Technology in Islamic boarding schools can improve access, learning resources, and student involvement. The flow of information encourages the search for truth, including in Islamic religious education. The method used in this paper is a literature study, with data collection through understanding and reviewing theories from various relevant literature. The data analysis technique uses document analysis which not only records information, but also understands the hidden meaning in the document carefully and critically. The results of this paper show that Fazlur Rahman emphasizes the balance between maintaining Islamic values ​​and adapting to technology in Islamic boarding school education. He applies technology integration to improve learning without sacrificing the idealism of Islamic boarding schools, with a healthy environment, competent educators, and preservation of Islamic moral values. This approach allows Islamic boarding schools to produce a generation that is faithful, intelligent, and ready to face digital challenges.